Herbicidal Formulations with Plant-Based Compounds to Control Amaranthus hybridus, Lolium multiflorum, and Brassica rapa Weeds - Romero, Juan José (2025)
Numerous studies have shown the potential effect of bioactive agents againstweeds. In this study, we developed two binary formulations with nonanoic acid, citral, orthymoquinone as herbicides and evaluated their physicochemical properties. The presenceof the bioactive compounds in the formulations was confirmed through FTIR spectroscopy.A dynamic light scattering study was conducted to characterize the emulsified formulationsand the size and distribution of the aggregates. In addition, thermogravimetric analysis wasperformed to ensure the thermal stability of the formulations. The herbicidal activity againstAmaranthus hybridus, Lolium multiflorum, and Brassica rapa weeds was evaluated, and eachspecies showed different levels of sensitivity with half maximal inhibitory concentrationdoses from 0.07 to 5 mM. The binary formulations negatively affected the photosyntheticsystem reducing Fv/Fm values at 5 days after treatment. Lastly, the phytotoxic effect of theformulations was tested on wheat germination, and they did not inhibit plant germinationand seedling growth at ≤5 mM after 14 days of application. The development of newformulations with natural compounds as bioactive ingredients would allow control of awide spectrum of weeds through a multitarget-site effect.